Junie B. Jones is a Party Animal : Junie B. Jones #10 - Park, Barbara, 1947-; Brunkus, Denise (New York : Random House, 1997)
Lucille invites Junie B. and her friend Grace to sleep over at her very rich nanna's house, where everything is beautiful, expensive, and breakable.
"A Stepping Stone book."
"RL:2.3 006-009"--P. [4] of cover.
Keywords: Grandmothers -- Juvenile fiction; Wealth -- Juvenile fiction